Variability reduction in stencil printing of solder paste for surface mount technology - Ibrahim, Mustaffa (1998)
Competition in stencil printing to produce excellence in the finished product is intense. Faults in the printing process are a major source of board failure. Studies have shown that over 63% of defects identified after reDow originated from the solder paste printing ( A. Lotfi ,1998 ) . However. understanding these failures are a challenging problem as the printing process has a large number of non linearly dependent variables such as factors relating to paste (formulation. viscosity), the environment (temperature, humidity) and machine parameter (alignment, pressure and speed of squeegee, blade hardness etc). The process engineer is challenged to widen the process window so that future modifications to the process, such as the addition of a new component, can be achieved with little. if any, change in materials or process parameters. This thesis reports the effect of temperature and humidity variation from the manufacturing environment on the solder paste consistency and optimization of the essential parameters of squeegee pressure, squeegee speed. separation speed and print gap. The outcome of variation in temperature and humidity to the solder paste viscosity were analyzed and tests were done to determine the characteristic of the solder paste. The tests results indicate that the temperature and humidity has an impact on the solder paste printability. thus some attempts must be taken to control these variables. For parameter optimization. the analysis was carried out using statistical optimization. The main aim was to combine these parameters with three main pitch categories to produce the acceptable print formation. The results showed that. the ideal print result requires optimum statistical combinations of four parameters essentially related to a particular pitch. It is also shown that there is a diversity and contrasts of the combination of the parameters for each category of pitch. Detailed explanations as to the phenomenon are outlined in the thesis.